Internship Program For Students With Disabilities: Are Malaysian Family Ready? - Zainal, Mohd Syazwan; Pa, Wan Ahmad Munsif Wan; Mahmud, Muhammad Sofwan (The journal of contemporary issues in business and government, 2021)
The difficulty faced by people with disabilities (PWDs) in the job market is an issue that must be taken seriously. Career transition is a program that can provide an opportunity for students with disabilities (SWDs) to acquire relevant skills and gain work experience before entering the real world of work. Through the career transition program (CTP), the SWDs will undergo an internship program for a specified time after mastering the required job-related skills. However, family engagement is important in ensuring the success of this program. Family engagement included three aspects which are family involvement, family empowerment, and family preparation. The internship at the actual workplace has provided the platform for the SWDs not only to experience real working life but also to build their capabilities that meet the requirements and demands of the employers, this article discusses how families need to understand their role in CTP so that the internship program can have a positive impact on PWDs. Further research suggestions are also discussed in this article.